(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Comprehensive automobile insurance is considered as an important insurance which is managing by National Insurance Company due to the continuous accidents the company is endeavoring to this market not for trading motives only but also to increase the insurance awareness of people and insurance benefit for other insurance portfolios .On this basis the researcher had chosen her subject ( obstacles in marketing comprehensive automobile Insurance policy ) the company faces several obstacles and limitations in marketing the policies of this portfolio due to certain factors and influences beyond the mainly connected with the reduction of marketing programmes of the company . the aim of this study is to shade the light upon the internal factors which can be governed by the company confronted and solved .